2008
DOI: 10.1016/j.brainres.2008.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Group independent component analysis reveals consistent resting-state networks across multiple sessions

Abstract: Group independent component analysis (gICA) was performed on resting-state data from 14 healthy subjects scanned on 5 fMRI scan sessions across 16 days. The data were reduced and aggregated in 3 steps using Principal Components Analysis (PCA, within scan, within session and across session) and subjected to gICA procedures. The amount of reduction was estimated by an improved method that utilizes a first-order autoregressive fitting technique to the PCA spectrum. Analyses were performed using all sessions in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 43 publications
4
83
2
1
Order By: Relevance
“…Our networks have been also reported in a number of previous resting state studies (Beckmann et al 2005;Chen et al 2008;Damoiseaux et al 2006;De Luca et al 2006;Mantini et al 2007;van den Heuvel et al 2008), although there is no complete consensus on the number and topology of the RSNs.…”
Section: Analysis Of Resting State Networksupporting
confidence: 64%
See 2 more Smart Citations
“…Our networks have been also reported in a number of previous resting state studies (Beckmann et al 2005;Chen et al 2008;Damoiseaux et al 2006;De Luca et al 2006;Mantini et al 2007;van den Heuvel et al 2008), although there is no complete consensus on the number and topology of the RSNs.…”
Section: Analysis Of Resting State Networksupporting
confidence: 64%
“…ICA is a method capable of separating independent spatio-temporal patterns of synchronized neural activity from fMRI data (Bartels and Zeki 2005), without prior knowledge about their activity waveforms or locations (McKeown et al 1998). Numerous authors demonstrated that voxels belonging to a given ICA network have higher BOLD temporal correlations among themselves compared with voxels belonging to other patterns, making ICA particularly suitable for functional connectivity studies (Beckmann et al 2005;Chen et al 2008;Damoiseaux et al 2006;De Luca et al 2006;Greicius et al 2004;Jafri et al 2008;Mantini et al 2007;Stevens et al 2009). Using ICA, we obtained reproducible RSN spatial maps across subjects, along with their associated time-courses, which could be used for effective connectivity analysis.…”
Section: Methodologic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human brain has been shown to be composed of multiple coherent networks that support sensory, motor and cognitive functions (Buzsáki and Draguhn, 2004;De Luca et al, 2006;Smith et al, 2009). These brain networks appear to be consistent across time within and between individuals (Chen et al, 2008;Damoiseaux et al, 2006), and constrained to anatomically connected regions (Greicius et al, 2009;Honey et al, 2009). Interestingly, the strength of functional connectivity in these networks at "rest" is able to predict relevant task-induced activation and behavioral performance (Hampson et al, 2006;Zou et al, in press).…”
Section: Introductionmentioning
confidence: 97%
“…These networks have been shown to be consistent across time (Chen et al, 2008) and across subjects (Damoiseaux et al, 2006). While investigations into these ''intrinsic connectivity networks'' (Seeley et al, 2007) have harnessed other imaging modalities such as EEG and PET, fMRI has been the tool of choice for the majority of research in this area (Smith et al, 2009).…”
mentioning
confidence: 99%